The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s0033291722002185
|View full text |Cite
|
Sign up to set email alerts
|

Between- and within-person effects of stress on emotional eating in women: a longitudinal study over 49 days

Abstract: Background Stress is associated with binge eating and emotional eating (EE) cross-sectionally. However, few studies have examined stress longitudinally, limiting understanding of how within-person fluctuations in stress influence EE over time and whether stress is a risk factor or consequence of EE. Additionally, little is known regarding how the biological stress response relates to EE. Methods We used an intensive, longitudinal design to examine between-person and within-person effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Financial hardship is typically accompanied by considerable psychological stress (Frankham et al, 2020), which is a substantial risk factor for BE (e.g., Fowler et al, 2022;Smith et al, 2021). Interestingly, we found that a measure of general COVID-19 related distress (i.e., "What level of stress and/or distress did you feel TODAY in relation to COVID-19?")…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Financial hardship is typically accompanied by considerable psychological stress (Frankham et al, 2020), which is a substantial risk factor for BE (e.g., Fowler et al, 2022;Smith et al, 2021). Interestingly, we found that a measure of general COVID-19 related distress (i.e., "What level of stress and/or distress did you feel TODAY in relation to COVID-19?")…”
Section: Discussionmentioning
confidence: 71%
“…Several potential mechanisms could underlie an association between financial hardship and BE phenotypes during COVID‐19. Financial hardship is typically accompanied by considerable psychological stress (Frankham et al, 2020 ), which is a substantial risk factor for BE (e.g., Fowler et al, 2022 ; Smith et al, 2021 ). Interestingly, we found that a measure of general COVID‐19 related distress (i.e., “What level of stress and/or distress did you feel TODAY in relation to COVID‐19?”) was not significantly correlated with financial hardship in our study ( r = .02, p = .810), indicating the need for measures that tap psychological stress related to financial concerns in particular.…”
Section: Discussionmentioning
confidence: 99%
“…This association is only marginally translated to the between-person level; people who tend to experience stressors more often over the study period, or to report more unpleasant levels, had slightly higher levels of food cravings, but this became non-significant after accounting for age, BMI and gender in sensitivity checks. It could be that the experience of a stressor triggers an immediate increase in distress and consequently an immediate willingness to eat in order to diminish such distress (Fowler et al, 2022;Klatzkin et al, 2022), and so the cravings are quickly resolved. Further research could explore whether negative emotions mediate the within-person relationship between a stressor experience and food craving.…”
Section: Discussionmentioning
confidence: 99%
“…During stressful experiences or periods, people might have difficulties distinguishing between hunger and distress resulting in overeating (Bruch, 1961;Kaplan & Kaplan, 1957), and may want to eat as a way to escape or avoid distress (Heatherton & Baumeister, 1991), or to seek emotional relief (Fowler et al, 2022;Klatzkin et al, 2022). Additionally, not all events will result in a similar stressful response and health impact (Cohen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…That is, core symptoms refer to the increased amount of food intake and the fact that the consumption continues in spite of knowledge of adverse consequences. Both symptoms can be found in individuals that exhibit binge and emotional eating behaviours, both of which showed clear associations with stress (Fowler et al., 2022; Rosenbaum & White, 2015; van Strien, 2018). Furthermore, studies suggested that mindfulness‐based interventions can reduce both forms of disordered eating (Katterman et al., 2014).…”
Section: Introductionmentioning
confidence: 99%